The determinants of livestock prices in Niger - Fafchamps, M.; Gavian, S. (International Livestock Research Institute, 1998)
In the highly risky environment of the Sahel, livestock play an important role as a form of insurance against weather risk in addition to their important contributions to rural incomes, urban meat supply and export earnings. Most Sahelian farmers and pastoralists pursue production strategies that seek to minimise risk associated with adverse climatic conditions. To be effective, traditional strategies of this kind require livestock prices to be relatively stable. This condition has, however, rarely been met in the Sahel under severe crisis conditions like drought or economic disruption where food entitlement failures and collapses in livestock-grain terms of trade have occurred. An issue which has not received adequate attention in the analysis of drought prone livestock economies of the Sahel is that weather is probably not the only culprit for food entitlement failures. Macro-economic conditions and other factors affecting the livestock sector also play an important role through their effect on urban demand for meat, livestock prices, and thus the value of assets liquidated by farmers and pastoralists in hard times. Knowledge and understanding of livestock price developments and their determinants in a Sahelian context where traditional adjustments to weather risk over time and space coexist with rising urban demand for meat therefore provide a key input to early warning, market and trade policies. This paper discusses livestock price developments in Niger, the determinants of livestock prices and market integration. It shows that livestock prices in Niger, a representative Sahelian country, respond not only to weather stocks but also to shifts in the rural and urban demand for meat in the country and in neighbouring Nigeria. The basis for 15 animal categories collected monthly in 38 districts of Niger over a period of 21 years.